A method for preparing a bioactive glass fiber reinforced polylactic acid composite material

By plasma treatment of bioactive glass fibers and compounding with chitosan and sodium tripolyphosphate, the problem of easy agglomeration of bioactive glass powders is solved, and the mechanical strength and biocompatibility of polylactic acid materials are significantly improved.

CN119158087BActive Publication Date: 2025-04-01ZHEJIANG CANWELL MEDICAL DEVICES CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411652551.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-04-01
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

When existing bioactive glasses are combined with polylactic acid materials, the bioactive glass powder is prone to agglomeration and difficult to mix evenly, and the mechanical strength enhancement effect is not significant, which cannot meet the needs of high strength and high stiffness.

Method used

The bioactive glass fiber is compounded with polylactic acid material after plasma treatment, and the compatibility and binding stability of the fibers with polylactic acid are improved through the medium of chitosan and sodium tripolyphosphate, thereby improving the mechanical strength and biocompatibility.

Benefits of technology

The tensile strength and bending strength of polylactic acid materials are significantly improved, the binding properties of bioactive glass fibers and polylactic acid are enhanced, and the mechanical properties and biocompatibility of the materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of medical materials, and discloses a method for preparing a bioactive glass fiber reinforced polylactic acid composite material, comprising the following steps: (1) subjecting the bioactive glass fiber to plasma treatment; (2) dissolving chitosan in an acetic acid aqueous solution, and then adding the treated bioactive glass fiber to obtain a mixed solution I; (3) adding the bioactive glass powder to a sodium tripolyphosphate aqueous solution, and then ball milling to obtain a mixed solution II; (4) gradually adding the mixed solution II to the mixed solution I, while stirring, and continuing to stir overnight after completion; then filtering and drying to obtain a modified glass fiber; (5) mixing the modified glass fiber and polylactic acid particles and then melt-extruding to obtain a polylactic acid composite material. The present invention can significantly improve the mechanical strength of the composite material by compounding the modified bioactive glass fiber with the polylactic acid material, and can thus be better used as an orthopedic implant material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical materials, and in particular to a method for preparing a bioactive glass fiber reinforced polylactic acid composite material. Background Art

[0002] Polylactic acid (PLA) or polylactic acid derivatives (such as PLGA) as orthopedic implant materials have the advantages of good biodegradability, biocompatibility and adjustable degradation rate. However, their weak mechanical properties, acidic environment caused by degradation products and low biological activity limit their application. Therefore, it is usually necessary to compound polylactic acid materials with other materials to enhance their performance.

[0003] Bioactive glass (BAG) has excellent biological activity and can quickly induce the formation of hydroxyapatite (HA) layer in body fluids, promote the adhesion and growth of bone cells, and promote bone tissue regeneration. At the same time, bioactive glass has good compatibility with human tissues, which can reduce the rejection reaction of tissues after implantation and improve the biocompatibility of materials. Therefore, the composite of bioactive glass and polylactic acid material can significantly improve the performance of the material in many aspects and enhance its application in the biomedical field.

[0004] However, bioactive glass is usually compounded with polylactic acid material in the form of powder, and bioactive glass is very easy to agglomerate and difficult to mix evenly. In addition, the bioactive glass powder does not significantly improve the mechanical strength of polylactic acid material, and thus cannot meet the demand for high-strength and high-rigidity polylactic acid composite materials. For example, the invention patent with publication number CN104524637A discloses a polymer bioceramic composite nanoparticle biodegradable scaffold and its preparation method, including biodegradable medical devices such as scaffolds made of biodegradable polymer bioceramic nanoparticle composites; the invented medical device includes at least one bioceramic nanoparticle dispersed in (at least) one biodegradable polymer; the biodegradable polymer includes but is not limited to biodegradable polyester; the method and equipment for dispersing one or more bioceramic nanoparticles in the polymer are not the same. The bioceramic nanoparticles here include but are not limited to amorphous calcium phosphate (ACP), dicalcium phosphate (DCP), tricalcium phosphate (TCP), hydroxyapatite pentacalcium (HAP), tetracalcium phosphate carbon monoxide (TTCP) and a combination of the above substances or equivalent substances. This method disperses bioceramic particles in a biodegradable polymer, which is highly susceptible to agglomeration and will result in low mechanical strength. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a bioactive glass fiber reinforced polylactic acid composite material, by compounding the modified bioactive glass fiber with the polylactic acid material, the compatibility and dispersibility of the bioactive glass fiber in the polylactic acid matrix are improved, while the bonding stability is improved, thereby further improving the mechanical strength and biocompatibility, which is conducive to better application as an orthopedic implant material.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] The present invention provides a method for preparing a bioactive glass fiber reinforced polylactic acid composite material, comprising the following steps:

[0008] (1) Plasma treatment of bioactive glass fibers with a diameter of 10-20 μm and a length of 1-3 mm;

[0009] (2) dissolving chitosan in an acetic acid aqueous solution, and then adding the treated bioactive glass fiber to obtain a mixed solution I;

[0010] (3) adding the bioactive glass powder into the sodium tripolyphosphate aqueous solution, and then ball milling to obtain a mixed solution II;

[0011] (4) gradually adding the mixed solution II into the mixed solution I while stirring, and continuing to stir overnight after completion, and then filtering and drying to obtain modified glass fiber;

[0012] (5) The modified glass fiber and polylactic acid particles are mixed in a mass ratio of 5-20:100 and then melt-extruded to obtain a polylactic acid composite material.

[0013] The bioactive glass is made into fibers and then compounded with polylactic acid material. Since glass fiber has high tensile strength and modulus, the introduction of bioactive glass fiber into the composite material can significantly improve the tensile strength and flexural strength of PLA. In addition, BAG fiber also has good bioactivity and biocompatibility. Therefore, the resulting composite material can be better used as an orthopedic implant material.

[0014] However, there are greater compatibility issues between bioactive glass fibers and polylactic acid materials, and there will also be a certain agglomeration effect. The present invention plasma treats the bioactive glass fibers so that the fiber surface has abundant carboxyl and hydroxyl groups, which is beneficial to improving its compatibility with polylactic acid materials. In addition, the treated bioactive glass fibers can react and combine with chitosan through active groups. After chitosan is treated in a dilute acid solvent, it can be transformed from a highly curled molecular conformation to a stretched molecular chain conformation, and then the stretched chitosan molecular chain can be grafted on the surface of the bioactive glass fibers. Afterwards, by adding bioactive glass powder modified by sodium tripolyphosphate surface coating, cross-linking can be performed on the grafted chain, the bioactive glass particles are fixed to the surface of the bioactive glass fibers, and space intervals are formed by the chitosan molecular chains, which is beneficial to reduce agglomeration and improve dispersibility. In addition, the introduction of chitosan macromolecules can also improve the mechanical strength of the composite material. The good compatibility between chitosan and polylactic acid molecules, as well as the covalent bond between active groups, can greatly improve the binding between bioactive glass fibers and polylactic acid. The bioactive glass particles have a higher binding stability due to the entanglement of molecular chains, which can further improve the mechanical strength.

[0015] Preferably, in step (1), the bioactive glass fiber is obtained by melt drawing of bioactive glass powder.

[0016] Preferably, in step (1), the plasma treatment is performed by using oxygen and argon in a volume ratio of 1-3:1 and a gas flow rate of 10-50 cm 3 / min, the processing pressure is 10-100Pa, the processing temperature is 40-60℃, the processing power is 50-200W, and the processing time is 5-20min.

[0017] Preferably, in step (2), the mass concentration of the acetic acid aqueous solution is 1-2%.

[0018] Preferably, in step (2), the ratio of the added amounts of chitosan, acetic acid aqueous solution and treated bioactive glass fiber is 80-100 mg:50 mL:1 g.

[0019] Preferably, in step (3), the concentration of the sodium tripolyphosphate aqueous solution is 40-60 mg / mL; and the ratio of the added amount of the bioactive glass powder to the sodium tripolyphosphate aqueous solution is 0.07-0.1 g:1 mL.

[0020] Preferably, in step (3), the particle size of the bioactive glass powder is 30-50 nm.

[0021] Preferably, in step (3), the ball milling is performed at a rotation speed of 100-200 rpm for 10-30 min.

[0022] Preferably, in step (4), the volume ratio of the mixed solution II to the mixed solution I is 1:1.

[0023] Preferably, in step (4), the stirring speed is 500-800 rpm, and the addition time of mixed solution II is 40-60 min.

[0024] Preferably, in step (5), the mass ratio of the modified glass fiber to the polylactic acid particles is 10-20:100.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) Bioactive glass fiber has good bioactivity and biocompatibility. Since glass fiber has high tensile strength and modulus, compounding it with polylactic acid material can significantly improve the tensile strength and flexural strength of PLA.

[0027] (2) By first grafting extended chitosan molecular chains on the surface of bioactive glass fibers, and then adding bioactive glass powder modified by sodium tripolyphosphate surface coating, cross-linking can be carried out on the grafted chains to fix the bioactive glass particles on the surface of the bioactive glass fibers, and space intervals are formed by the chitosan molecular chains, which is beneficial to reduce agglomeration and improve dispersibility;

[0028] (3) The introduction of chitosan as a macromolecule can improve the mechanical strength of the composite material. The good compatibility between chitosan and polylactic acid molecules, as well as the covalent bonding between active groups, can greatly improve the binding between bioactive glass fibers and polylactic acid. The bioactive glass particles have a higher bonding stability due to the entanglement of molecular chains, which can further improve the mechanical strength. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0030] A method for preparing a bioactive glass fiber reinforced polylactic acid composite material comprises the following steps:

[0031] (1) Place the bioactive glass powder in a crucible and heat it to 1200-1400℃ to completely melt it to form a uniform glass melt, and keep it in the molten state for 30-50 minutes to eliminate bubbles and ensure uniform composition; melt the molten glass melt and draw it into a wire, while cooling it with nitrogen, and then ultrasonically clean and dry it with ethanol, and cut it to obtain bioactive glass (BAG) fibers with a diameter of 10-20μm and a length of 1-3mm. Then use plasma to treat the bioactive glass fiber, using oxygen and argon in a volume ratio of 1-3:1, and a gas flow rate of 10-50cm 3 / min, the processing pressure is 10-100Pa, the processing temperature is 40-60℃, the processing power is 50-200W, and the processing time is 5-20min.

[0032] (2) Dissolve chitosan in an acetic acid aqueous solution with a mass concentration of 1-2%, then add the treated bioactive glass fiber and stir for 30-60 minutes. The ratio of chitosan, acetic acid aqueous solution and treated glass fiber added is 80-100 mg:50 mL:1 g to obtain a mixed solution I.

[0033] (3) Add the bioactive glass powder to a sodium tripolyphosphate aqueous solution having a concentration of 40-60 mg / mL, wherein the ratio of the bioactive glass powder to the sodium tripolyphosphate aqueous solution is 0.07-0.1 g:1 mL, and then ball mill at a rotation speed of 100-200 rpm for 10-30 min to obtain a mixed solution II.

[0034] (4) gradually adding the mixed solution II into the mixed solution I while stirring at a speed of 500-800 rpm, the volume ratio of the mixed solution II to the mixed solution I being 1:1, the adding time of the mixed solution II being controlled to be 40-60 min, and stirring being continued overnight after the addition is completed; then filtering and drying to obtain the modified glass fiber;

[0035] (5) The modified glass fiber and polylactic acid particles are mixed in a mass ratio of 5-20:100 and then melt-extruded to obtain a polylactic acid composite material.

[0036] In a specific embodiment of the present invention, in step (1), the particle size of the bioactive glass powder is nanometer or micrometer scale.

[0037] In a specific embodiment of the present invention, in step (2), the deacetylation degree of chitosan is 90% or more, and the weight average molecular weight is 100,000-300,000.

[0038] In a specific embodiment of the present invention, in step (3), the particle size of the bioactive glass powder is 30-50 nm.

[0039] In a specific embodiment of the present invention, in step (4), the rate of adding mixed solution II is uniform.

[0040] In a specific embodiment of the present invention, in step (5), the weight average molecular weight of the polylactic acid particles is 200,000-400,000.

[0041] In a specific embodiment of the present invention, in step (5), the temperature for mixing and melt-extruding the modified glass fiber and the polylactic acid particles is 170-190°C.

[0042] Example 1

[0043] (1) The bioactive glass powder (45S5) was heated to 1300°C to completely melt it, and the molten state was maintained for 30 minutes. Then, the fiber was melted and cooled with nitrogen. Then, it was ultrasonically cleaned with ethanol, dried, and cut to obtain bioactive glass (BAG) fibers with a diameter of 15±1μm and a length of 2mm. The bioactive glass fibers were then treated with plasma using oxygen and argon in a volume ratio of 2:1 and a gas flow rate of 25cm 3 / min, the processing pressure is 60Pa, the processing temperature is 50℃, the processing power is 120W, and the processing time is 15min.

[0044] (2) Dissolve 100 mg of chitosan (deacetylation degree 95%, weight average molecular weight 100,000) in 50 mL of 1% acetic acid aqueous solution, add 1 g of treated bioactive glass fiber and stir for 30 min to obtain mixed solution I.

[0045] (3) Add 3.5 g of bioactive glass powder (45S5) with a particle size of 30-50 nm and an average particle size of 45 nm into 50 mL of a 60 mg / mL sodium tripolyphosphate aqueous solution, stir evenly, and then ball mill at a speed of 140 rpm for 25 min to obtain mixed solution II.

[0046] (4) Adding mixed solution II gradually into mixed solution I while stirring at a speed of 600 rpm. The volume ratio of mixed solution II to mixed solution I is 1:1. The total addition time of mixed solution II is controlled to be 45 min. After completion, stirring is continued overnight. The modified glass fiber is then filtered, washed with ethanol aqueous solution, and dried to obtain the modified glass fiber.

[0047] (5) The modified glass fiber and polylactic acid particles (weight average molecular weight of 300,000) in a mass ratio of 10:100 were melt-blended at 170°C and extruded using a twin-screw extruder to obtain a polylactic acid composite material.

[0048] Example 2

[0049] (1) The bioactive glass powder (45S5) was heated to 1300°C to completely melt it and kept in the molten state for 30 minutes. It was then melt-drawn and cooled with nitrogen. It was then ultrasonically cleaned with ethanol, dried, and cut to obtain bioactive glass (BAG) fibers with a diameter of 12±1μm and a length of 3mm. The bioactive glass fibers were then treated with plasma using oxygen and argon in a volume ratio of 3:1 and a gas flow rate of 35cm 3 / min, the processing pressure is 50Pa, the processing temperature is 50℃, the processing power is 150W, and the processing time is 15min.

[0050] (2) Dissolve 100 mg of chitosan (deacetylation degree 95%, weight average molecular weight 100,000) in 50 mL of 1% acetic acid aqueous solution, add 1 g of treated bioactive glass fiber and stir for 30 min to obtain mixed solution I.

[0051] (3) Add 3.5 g of bioactive glass powder (45S5) with a particle size of 30-50 nm and an average particle size of 45 nm into 50 mL of a 60 mg / mL sodium tripolyphosphate aqueous solution, stir evenly, and then ball mill at a speed of 140 rpm for 25 min to obtain mixed solution II.

[0052] (4) Adding mixed solution II gradually into mixed solution I while stirring at a speed of 600 rpm. The volume ratio of mixed solution II to mixed solution I is 1:1. The total addition time of mixed solution II is controlled to be 45 min. After completion, stirring is continued overnight. The modified glass fiber is then filtered, washed with ethanol aqueous solution, and dried to obtain the modified glass fiber.

[0053] (5) The modified glass fiber and polylactic acid particles (weight average molecular weight of 300,000) in a mass ratio of 10:100 were melt-blended at 170°C and extruded using a twin-screw extruder to obtain a polylactic acid composite material.

[0054] Example 3

[0055] (1) The bioactive glass powder (45S5) was heated to 1300°C to completely melt it, and the molten state was maintained for 30 minutes. Then, the fiber was melted and cooled with nitrogen. Then, it was ultrasonically cleaned with ethanol, dried, and cut to obtain bioactive glass (BAG) fibers with a diameter of 15±1μm and a length of 2mm. The bioactive glass fibers were then treated with plasma using oxygen and argon in a volume ratio of 2:1 and a gas flow rate of 25cm 3 / min, the processing pressure is 60Pa, the processing temperature is 50℃, the processing power is 120W, and the processing time is 15min.

[0056] (2) Dissolve 100 mg of chitosan (deacetylation degree 95%, weight average molecular weight 100,000) in 50 mL of 1% acetic acid aqueous solution, add 1 g of treated bioactive glass fiber and stir for 30 min to obtain mixed solution I.

[0057] (3) 4 g of bioactive glass powder (45S5) with a particle size of 30-50 nm and an average particle size of 35 nm was added to 50 mL of a 50 mg / mL sodium tripolyphosphate aqueous solution, and then ball milled at 200 rpm for 20 min to obtain a mixed solution II.

[0058] (4) gradually adding mixed solution II into mixed solution I while stirring at a speed of 600 rpm. The volume ratio of mixed solution II to mixed solution I is 1:1. The total addition time of mixed solution II is controlled to be 60 min. After completion, stirring is continued overnight. The modified glass fiber is then filtered, washed with ethanol aqueous solution, and dried to obtain the modified glass fiber.

[0059] (5) The modified glass fiber and polylactic acid particles (weight average molecular weight of 300,000) in a mass ratio of 15:100 were melt-blended at 170°C and extruded using a twin-screw extruder to obtain a polylactic acid composite material.

[0060] Example 4

[0061] (1) The bioactive glass powder (45S5) was heated to 1300°C to completely melt it, and the molten state was maintained for 30 minutes. Then, the fiber was melted and cooled with nitrogen. Then, it was ultrasonically cleaned with ethanol, dried, and cut to obtain bioactive glass (BAG) fibers with a diameter of 15±1μm and a length of 2mm. The bioactive glass fibers were then treated with plasma using oxygen and argon in a volume ratio of 2:1 and a gas flow rate of 25cm 3 / min, the processing pressure is 60Pa, the processing temperature is 50℃, the processing power is 120W, and the processing time is 15min.

[0062] (2) Dissolve 80 mg of chitosan (deacetylation degree 95%, weight average molecular weight 100,000) in 50 mL of 2% acetic acid aqueous solution, add 1 g of the treated bioactive glass fiber and stir for 40 min to obtain mixed solution I.

[0063] (3) Add 5 g of bioactive glass powder (45S5) with a particle size of 30-50 nm and an average particle size of 35 nm into 50 mL of a 40 mg / mL sodium tripolyphosphate aqueous solution, and then ball mill at 200 rpm for 30 min to obtain a mixed solution II.

[0064] (4) gradually adding mixed solution II into mixed solution I while stirring at a speed of 800 rpm. The volume ratio of mixed solution II to mixed solution I is 1:1. The total addition time of mixed solution II is controlled to be 40 min. After completion, stirring is continued overnight. The modified glass fiber is then filtered, washed with ethanol aqueous solution, and dried to obtain the modified glass fiber.

[0065] (5) The modified glass fiber and polylactic acid particles (weight average molecular weight of 300,000) in a mass ratio of 20:100 were melt-blended at 170°C and extruded using a twin-screw extruder to obtain a polylactic acid composite material.

[0066] Comparative Example 1

[0067] The difference from Example 1 is that bioactive glass fiber is directly compounded with polylactic acid.

[0068] (1) The bioactive glass powder (45S5) was heated to 1300°C to completely melt it, and the molten state was maintained for 30 minutes. Then, the fiber was melted and cooled with nitrogen. Then, it was ultrasonically cleaned with ethanol, dried, and cut to obtain bioactive glass (BAG) fibers with a diameter of 15±1μm and a length of 2mm. The bioactive glass fibers were then treated with plasma using oxygen and argon in a volume ratio of 2:1 and a gas flow rate of 25cm 3 / min, the processing pressure is 60Pa, the processing temperature is 50℃, the processing power is 120W, and the processing time is 15min.

[0069] (2) The treated bioactive glass fibers and polylactic acid particles in a mass ratio of 10:100 were melt-blended at 170° C. and extruded using a twin-screw extruder to obtain a polylactic acid composite material.

[0070] Comparative Example 2

[0071] The difference from Example 1 is that the chitosan has a lower deacetylation degree and a larger molecular weight.

[0072] (1) The bioactive glass powder (45S5) was heated to 1300°C to completely melt it, and the molten state was maintained for 30 minutes. Then, the fiber was melted and cooled with nitrogen. Then, it was ultrasonically cleaned with ethanol, dried, and cut to obtain bioactive glass (BAG) fibers with a diameter of 15±1μm and a length of 2mm. The bioactive glass fibers were then treated with plasma using oxygen and argon in a volume ratio of 2:1 and a gas flow rate of 25cm 3 / min, the processing pressure is 60Pa, the processing temperature is 50℃, the processing power is 120W, and the processing time is 15min.

[0073] (2) Dissolve 100 mg of chitosan (degree of deacetylation: 80%, weight average molecular weight: 500,000) in 50 mL of 1% acetic acid aqueous solution, then add 1 g of the treated bioactive glass fiber and stir for 30 min to obtain mixed solution I.

[0074] (3) Add 3.5 g of bioactive glass powder (45S5) with a particle size of 30-50 nm and an average particle size of 45 nm into 50 mL of a 60 mg / mL sodium tripolyphosphate aqueous solution, stir evenly, and then ball mill at a speed of 140 rpm for 25 min to obtain mixed solution II.

[0075] (4) Adding mixed solution II gradually into mixed solution I while stirring at a speed of 600 rpm. The volume ratio of mixed solution II to mixed solution I is 1:1. The total addition time of mixed solution II is controlled to be 45 min. After completion, stirring is continued overnight. The modified glass fiber is then filtered, washed with ethanol aqueous solution, and dried to obtain the modified glass fiber.

[0076] (5) The modified glass fiber and polylactic acid particles (weight average molecular weight of 300,000) in a mass ratio of 10:100 were melt-blended at 170°C and extruded using a twin-screw extruder to obtain a polylactic acid composite material.

[0077] Comparative Example 3

[0078] The difference from Example 1 is that the bioactive glass powder is treated with chitosan before being added.

[0079] (1) The bioactive glass powder (45S5) was heated to 1300°C to completely melt it, and the molten state was maintained for 30 minutes. Then, the fiber was melted and cooled with nitrogen. Then, it was ultrasonically cleaned with ethanol, dried, and cut to obtain bioactive glass (BAG) fibers with a diameter of 15±1μm and a length of 2mm. The bioactive glass fibers were then treated with plasma using oxygen and argon in a volume ratio of 2:1 and a gas flow rate of 25cm 3 / min, the processing pressure is 60Pa, the processing temperature is 50℃, the processing power is 120W, and the processing time is 15min.

[0080] (2) Dissolve 100 mg of chitosan (deacetylation degree: 95%, weight average molecular weight: 100,000) in 50 mL of 1% acetic acid aqueous solution to obtain mixed solution I.

[0081] (3) Add 3.5 g of bioactive glass powder (45S5) with a particle size of 30-50 nm and an average particle size of 45 nm into 50 mL of a 60 mg / mL sodium tripolyphosphate aqueous solution, stir evenly, and then ball mill at a speed of 140 rpm for 25 min to obtain mixed solution II.

[0082] (4) Add mixed solution II gradually into mixed solution I while stirring at a speed of 600 rpm. The volume ratio of mixed solution II to mixed solution I is 1:1. The total addition time of mixed solution II is controlled to be 45 min. After completion, add 1 g of treated bioactive glass fiber and continue stirring overnight. Then, filter, wash with ethanol aqueous solution, and dry to obtain modified glass fiber.

[0083] (5) The modified glass fiber and polylactic acid particles (weight average molecular weight of 300,000) in a mass ratio of 10:100 were melt-blended at 170°C and extruded using a twin-screw extruder to obtain a polylactic acid composite material.

[0084] Comparative Example 4

[0085] The difference from Example 1 is that the fiber size is too large.

[0086] (1) The bioactive glass powder (45S5) was heated to 1300°C to completely melt it, and the molten state was maintained for 30 minutes. Then, the fiber was melted and cooled with nitrogen. Then, it was ultrasonically cleaned with ethanol, dried, and cut to obtain bioactive glass (BAG) fibers with a diameter of 30±1μm and a length of 5mm. The bioactive glass fibers were then treated with plasma using oxygen and argon in a volume ratio of 2:1 and a gas flow rate of 25cm 3 / min, the processing pressure is 60Pa, the processing temperature is 50℃, the processing power is 120W, and the processing time is 40min.

[0087] (2) Dissolve 100 mg of chitosan (deacetylation degree 95%, weight average molecular weight 100,000) in 50 mL of 1% acetic acid aqueous solution, add 1 g of treated bioactive glass fiber and stir for 30 min to obtain mixed solution I.

[0088] (3) Add 3.5 g of bioactive glass powder (45S5) with a particle size of 30-50 nm and an average particle size of 45 nm into 50 mL of a 60 mg / mL sodium tripolyphosphate aqueous solution, stir evenly, and then ball mill at a speed of 140 rpm for 25 min to obtain mixed solution II.

[0089] (4) Adding mixed solution II gradually into mixed solution I while stirring at a speed of 600 rpm. The volume ratio of mixed solution II to mixed solution I is 1:1. The total addition time of mixed solution II is controlled to be 45 min. After completion, stirring is continued overnight. The modified glass fiber is then filtered, washed with ethanol aqueous solution, and dried to obtain the modified glass fiber.

[0090] (5) The modified glass fiber and polylactic acid particles (weight average molecular weight of 300,000) in a mass ratio of 10:100 were melt-blended at 170°C and extruded using a twin-screw extruder to obtain a polylactic acid composite material.

[0091] Comparative Example 5

[0092] The difference from Example 1 is that the concentration of mixed solution II is too high.

[0093] (1) The bioactive glass powder (45S5) was heated to 1300°C to completely melt it, and the molten state was maintained for 30 minutes. Then, the fiber was melted and cooled with nitrogen. Then, it was ultrasonically cleaned with ethanol, dried, and cut to obtain bioactive glass (BAG) fibers with a diameter of 15±1μm and a length of 2mm. The bioactive glass fibers were then treated with plasma using oxygen and argon in a volume ratio of 2:1 and a gas flow rate of 25cm 3 / min, the processing pressure is 60Pa, the processing temperature is 50℃, the processing power is 120W, and the processing time is 15min.

[0094] (2) Dissolve 100 mg of chitosan (deacetylation degree 95%, weight average molecular weight 100,000) in 50 mL of 1% acetic acid aqueous solution, add 1 g of treated bioactive glass fiber and stir for 30 min to obtain mixed solution I.

[0095] (3) Add 5.5 g of bioactive glass powder (45S5) with a particle size of 30-50 nm and an average particle size of 45 nm into 50 mL of a 75 mg / mL sodium tripolyphosphate aqueous solution, stir evenly, and then ball mill at a speed of 140 rpm for 25 min to obtain mixed solution II.

[0096] (4) Adding mixed solution II gradually into mixed solution I while stirring at a speed of 600 rpm. The volume ratio of mixed solution II to mixed solution I is 1:1. The total addition time of mixed solution II is controlled to be 45 min. After completion, stirring is continued overnight. The modified glass fiber is then filtered, washed with ethanol aqueous solution, and dried to obtain the modified glass fiber.

[0097] (5) The modified glass fiber and polylactic acid particles (weight average molecular weight of 300,000) in a mass ratio of 10:100 were melt-blended at 170°C and extruded using a twin-screw extruder to obtain a polylactic acid composite material.

[0098] The polylactic acid composite materials in Examples 1-4 and Comparative Examples 1-5 were prepared into strips by injection molding. The bending performance test standard was in accordance with GB / T 9341-2008, and the strip size was 80 mm×10 mm×4 mm. The tensile performance test standard was in accordance with GB / T1040.1-2018. The strip preparation standard was in accordance with GB / T 1040.2-2022, and the strip dimensions were l3: 75 mm, l1: 30 mm, r: 30 mm, l2: 58 mm, b2: 10 mm, b1: 5 mm, h: 3 mm, and L0: 25 mm.

[0099] Table 1

[0100]

[0101] As shown in Table 1, the bioactive glass fiber in the present invention is modified by chitosan and bioactive glass particles and then composited with polylactic acid material, which can significantly improve the mechanical strength and biocompatibility of PLA while improving the compatibility and dispersibility with polylactic acid. However, the bioactive glass fiber in Comparative Example 1 is not modified, but only plasma treated and then composited with polylactic acid material, and the mechanical strength of the composite material obtained is significantly reduced.

[0102] In addition, in Comparative Example 2, chitosan with a low degree of deacetylation and a large molecular weight is used for reaction, which will cause the chitosan macromolecular chain to be unable to present a stretched molecular chain conformation after acetic acid treatment, and more to be coated on the surface of the bioactive glass fiber, and it is impossible to form an effective space interval. When the subsequent bioactive glass particles are loaded, too much agglomeration will also be caused, which will eventually affect the dispersibility of the composite material and reduce the mechanical strength. In Comparative Example 3, the bioactive glass particles are added after being cross-linked and coated with chitosan and sodium tripolyphosphate, which will also cause their agglomeration on the bioactive glass fiber, and are not conducive to the interlacing and entanglement of the macromolecular chains between chitosan and polylactic acid, so the compatibility of the bioactive glass fiber in the polylactic acid material will be reduced, and the mechanical strength will also be reduced. The size of the bioactive glass fiber used in Comparative Example 4 is too large, which will cause the modification effect to deteriorate, especially its compatibility in the polylactic acid material will be greatly affected, which will affect the performance of the composite material. The concentration of bioactive glass powder and sodium tripolyphosphate in mixed solution II in Comparative Example 5 is too high, which will lead to excessive crosslinking and local agglomeration on the surface of the bioactive glass fiber, and similar to Comparative Examples 2-3, the mechanical strength of the obtained composite material is reduced.

[0103] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a bioactive glass fiber reinforced polylactic acid composite material, characterized in that: The steps include: (1) Plasma treatment of bioactive glass fibers with a diameter of 10-20 μm and a length of 1-3 mm; (2) dissolving chitosan in an acetic acid aqueous solution, wherein the chitosan has a deacetylation degree of 90% or more and a weight average molecular weight of 100,000 to 300,000; and then adding the treated bioactive glass fiber to obtain a mixed solution I; (3) adding the bioactive glass powder into the sodium tripolyphosphate aqueous solution, and then ball milling to obtain a mixed solution II; (4) gradually adding the mixed solution II into the mixed solution I while stirring, and continuing to stir overnight after completion, and then filtering and drying to obtain modified glass fiber; (5) The modified glass fiber and polylactic acid particles are mixed in a mass ratio of 5-20:100 and then melt-extruded to obtain a polylactic acid composite material.

2. The method for preparing the bioactive glass fiber reinforced polylactic acid composite material according to claim 1, characterized in that: In step (1), the plasma treatment is performed by using a mixture of oxygen and argon with a gas flow rate of 10-50 cm 3 / min, the processing pressure is 10-100Pa, the processing temperature is 40-60℃, and the processing time is 5-20min.

3. The method for preparing the bioactive glass fiber reinforced polylactic acid composite material according to claim 1, characterized in that: In step (2), the mass concentration of the acetic acid aqueous solution is 1-2%.

4. The method for preparing the bioactive glass fiber reinforced polylactic acid composite material according to any one of claims 1 to 3, characterized in that: In step (2), the ratio of the added amount of chitosan, acetic acid aqueous solution and treated bioactive glass fiber is 80-100 mg:50 mL:1 g.

5. The method for preparing the bioactive glass fiber reinforced polylactic acid composite material according to claim 1, characterized in that: In step (3), the concentration of the sodium tripolyphosphate aqueous solution is 40-60 mg / mL.

6. The method for preparing the bioactive glass fiber reinforced polylactic acid composite material according to claim 1, characterized in that: In step (3), the ratio of the added amount of the bioactive glass powder to the sodium tripolyphosphate aqueous solution is 0.07-0.1 g: 1 mL.

7. The method for preparing the bioactive glass fiber reinforced polylactic acid composite material according to claim 1, 5 or 6, characterized in that: In step (3), the particle size of the bioactive glass powder is 30-50 nm.

8. The method for preparing the bioactive glass fiber reinforced polylactic acid composite material according to claim 1, characterized in that: In step (3), the ball milling is performed at a rotation speed of 100-200 rpm for 10-30 min.

9. The method for preparing the bioactive glass fiber reinforced polylactic acid composite material according to claim 1 or 8, characterized in that: In step (4), the volume ratio of the mixed solution II to the mixed solution I is 1:1; the stirring speed is 500-800 rpm, and the addition time of the mixed solution II is 40-60 min.

Citation Information

Patent Citations

  • High-molecular biological ceramic composite nanometer particle biodegradable stent and manufacturing method thereof

    CN104524637A

  • High-thermal-conductivity glass fiber reinforced polypropylene composite material

    CN111892764A

  • Glass fiber reinforced polyether-ether-ketone composite material as well as preparation method and application thereof

    CN116328032A